Post‐Earthquake Fold Growth Imaged in the Qaidam Basin, China, With Interferometric Synthetic Aperture Radar. Issue 3 (25th March 2021) - Daout, Simon; Parsons, Barry; Walker, Richard
Abstract: Questions regarding the development of folds and their interactions with the seismic faults within thrust systems remain unanswered. However, estimating fault slip and earthquake hazards using surface observations and kinematic models of folding requires an understanding of how the shortening is accommodated during the different phases of the earthquake cycle. Here, we construct 16‐years of interferometric synthetic aperture radar time series across the North Qaidam thrust system (NE Tibet), where three Mw 6.3 earthquakes occurred along basement faults underlying shortened folded sediments. The analysis reveals spatio‐temporal changes of post‐earthquake surface displacement rates and patterns, which continue more than 10 years after the seismic events. The decomposition of the Sentinel‐1 ascending and descending line of sight velocities into vertical and shortening post‐earthquake components indicates that long‐term transient uplift and shortening is in agreement with the deformation that might be expected from kinematic models of folding. Long‐term uplift coincides spatially with young anticlines observed in the geomorphology, with steep gradients in the forelimbs, gentle gradients in the back‐limbs, an absence of subsidence in the footwalls, and higher gradients along interpreted bedding planes. Long‐term shortening is also different from the surface displacements expected for typical time‐varying creep on a narrow dislocation interface and shows rates higher than the average convergence across the whole region. These findings provide evidence for anelastic fold buckling during the post‐earthquake phase and highlight the contribution of distributed aseismic deformation to the growth of topography. Key Points: Sixteen years of post‐seismic transient deformations measured with interferometric synthetic aperture radar Spatio‐temporal changes of post‐seismic rates and patterns have been observed Anelastic bulk deformation of the medium in response to fault slip